Accounting for lattice coherency in a two-phase elastic-plastic self-consistent model for nickel-based superalloys. (November 2018) - Li, Hongjia; Ekh, Magnus; Colliander, Magnus Hörnqvist; Larsson, Fredrik
Abstract: A 2-site elastic-plastic self-consistent (EPSC) model is developed and implemented in order to account for crystallographic texture development and grain morphology evolution under strong correlations between neighbor grains of different phases, both in space and orientation. Predictions of the model adequately fit the published in situ neutron diffraction data for nickel-based superalloys at ambient and elevated temperatures, in which γ and γ ' phases exhibit exact cube-cube orientation relationship. Comparison with 2-site model (small strain algorithm, non-rotation scheme) and 1-site model (finite strain algorithm, co-rotation scheme) has been made, and the result shows that the present 2-site model (finite strain algorithm, rotation scheme) leads to better predictions in lattice strain evolution where both rotation of crystal lattice and correlation between inclusions are accounted for, especially when the applied strain is larger than 0.02 for transverse direction and 0.05 ∼ 0.18 for axial direction for the materials studied in this work. Based on a systematic study on the effects of grain-grain interaction and total grain number on the homogenized results, we found that transverse lattice strains of γ (200) and/or γ ' (100) are sensitive to the interplay between γ - γ ' interaction and evolution of grain orientation distribution with deformation, while that of γ (220) and γ ' (110) are sensitive to the initial crystallographic texture.